Anna versus Xenia. Pułapki biograficznej lektury Zamieci Stefana Żeromskiego - Utkowska, Beata (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
An attempt is undertaken in this paper to demonstrate what traps are inherent in a biographical reading of Stefan Żeromski’s Zamieć (Blizzard). The author traces relations between Anna Zawadzka (the writer’s partner) and Xenia Granowska (the novel’s protagonist) and reconstructs the background to the text. The analysis implies it would be far safer to treat Zamieć as a broadly-defined autobiographical novel than to build straightforward parallels between Anna and Xenia.